Synthesis and characterization of CuO nanoparticles utilizing waste fish scale and exploitation of XRD peak profile analysis for approximating the structural parameters - Mashrafi Bin Mobarak; Md. Sahadat Hossain; Fariha Chowdhury; Samina Ahmed (Arabian Journal of Chemistry, 2022)
In this research, we strived to utilize waste fish scale (labeo rohita) for synthesizing CuO nano-particles (CuO NPs), which gained much attention due to its distinctive properties and versatile applications. Upon the heat treatment, the collagen content of the fish scale got transformed into gelatin which in turn converted the precursor material into CuO NPs. The X-Ray diffraction (XRD) analysis confirmed the formation of CuO NPs and revealed the structure to be of monoclinic lattice. The structural parameters i.e. crystallite size, lattice parameters, microstrain, dislocation density was evaluated for the synthesized CuO NPs using the XRD data. Scherrer’s Method (SM), Scherrer Equation Average Method (SEAM), Linear Straight Line Method (LSLM), Straight Line Passing the Origin Method (SLPOM), Monshi Scherrer Method (MSM), Williamson-Hall Method (WHM), Size-Strain Plot Method (SSPM), Halder-Wagner Method (HWM) was exploited for the estimation of crystallite size. According to the calculations, the crystallite size was found to be 87 nm, 41 nm, 1980 nm, 62 nm, 66 nm, 28 nm, 13 nm, 13 nm respectively and the dislocation density was found to be 1.32 × 10-4, 5.95 × 10-4, 0.002 × 10-4, 2.60 × 10-4, 2.29 × 10-4, 12.75 × 10-4, 59.17 × 10-4 and 59.17 × 10-4 respectively. UV–Vis absorption analysis also confirmed the formation of CuO NPs based on the absorption peak at 262 nm (λmax) and Tauc Plot method was used to calculate the optical band gap which was 3.84 eV. Functional group, especially the Cu-O bonding was confirmed by the Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) data. Field Emission Scanning Electron Microscopy (FESEM) showed three different shapes of CuO NPs which was also confirmed by Transmission Electron Microscopy (TEM). Particle size was determined based on FESEM and TEM image using imageJ software and also by the Dynamic Light Scattering (DLS) technique. Thermal analysis showed a four stage weight loss in case of Thermogravimetric (TGA) analysis and three conversion steps was observed in Differential Scanning Calorimetric (DSC) analysis. Such synthesis pathway is evidently green and facile for synthesizing CuO NPs with potentiality of various applications and also utilization of waste fish scale is a perquisite.